METODE ISTIDLAL IMAM FAKHR AL-DIN AL-RAZI: Refleksi Pemikirannya dalam Kitab al-Mahshul fi ‘Ilm Ushul al-Fiqh - KHOLIL SYU'AIB (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2015)
Imam Fakhr al-Din al-Razi is a powerful cleric who widely mastered various branches of science, is also avery prolific scholar. He was preoccupied with alifetime of scientific activities, many essays he wrote, show the breadth of knowledge that he had. One of his works in the field of ushul al-fiqh is the book al-Mahshul fi 'Ilm Ushul al-Fiqh. The book is used as the main reference for Muslims in studying the science of ushul al-fiqh. The book has agreat contribution in the dynamics of the development of Islamic law. His ideas about the istidlal methods in the book of al-Mahshul which indicated him as an expert on ushul (ushuliyyun) are authoritative. Although he has been declared as aclass adherents Mutakallimun (Syafi'iyah flow) in the science of ushul al-fiqh, there are some ushul ideas he actually differed with Imam Shafi'i. He also tried to give a brilliant arguments against the concept of Syafi'iyah flow ushul fiqh which has none of the bigotry.